Effectiveness of LMS Assisted by Schoology on Parabolic Motion on Learning Outcomes of Health Vocational Students - Oktaviyanti, Dewi; Sukmawati, Sari Sri; Setyawati, Eni; Ratnasari, Diah; Fayanto, Suritno (Jurnal Penelitian Pendidikan Fisika, 2020)
This study proposed to determine the effectiveness of the Learning Management System (LMS) assisted Schoology on parabolic material in student learning outcomes at the SMK Bhakti Indonesia Medika Pacitan. The study was a pre-experimental design with one group pre-test post-test design. The sample of this research was students of X SMK Kesehatan Bhakti Indonesia Medika Pacitan. The data analysis in this study used the One-Sample T-Test with SPSS 23. Based on the result, the average percentage of increase in student learning outcomes using LMS assisted schoology on parabolic material was 25%. By using the One Sample T-Test the sig. (2-tailed) Value of 0,000 < 0,05, statistically, there was a difference between before and after using the LMS-assisted Schoology. The usability questionnaire showed that the average for each aspect is 79% (usefulness), 67.2% (ease of use), 67.50% (ease of learning), and 64% of students are satisfied (satisfaction).